Goodenough on the Beginnings of Christianity - Kraabel, A.T (Brown Judaic Studies, 2020)
Few scholars loom as large in the history of scholarship on ancient Judaism than does Erwin Ramsdell Goodenough (1893-1965). A professor at Yale University for forty years, Goodenough fundamentally changed our understanding of Jews in the Hellenistic world, even when his suggestions turned out to be incorrect. Best known for his monumental, Jewish Symbols in the Greco-Roman Period, Goodenough also wrote on Christian origins, developing his own theory in a series of essays. In Goodenough on the Beginnings of Christianity, A. T. Kraabel has collected and organized the most important of these essays, which even after half a century remain relevant and fruitful.